Engelbert Kaempfer's trip to Japan (1690-1692): drawings and notes on an impenetrable country - Sanz Guillén, Alejandro M. (Anales de Historia del Arte, 2020)
From 1639, and until de mid-nineteenth century, Japan maintained an isolationist foreign policy and all relations with the Western countries, originated nearly one hundred years before, were broken. The Japanese government only made an exception with the Dutch East India Company, who had the privilege of being the only Europeans with access to the Japanese archipelago. Thanks to this prerogative, between 1690 and 1692, the German doctor Engelbert Kaempfer was able to visit the Land of the Rising Sun, traveling twice to the court of the sogún in Edo (Tokyo). As a result of these experiences, he took annotations and made drawings portraying several characteristics of those inaccessible islands. Many of these materials were published years after in his book The History of Japan (London, 1727). Nevertheless a large number of his designs, of incalculable historical value, remained unedited in the shadows of his archives. In this paper, we will try to shed light upon these sketches and illustrations. A partir de 1639, y hasta mediados del siglo XIX, Japón mantuvo una política aislacionista rompiendo todas las relaciones con Occidente originadas casi un siglo atrás. El gobierno nipón únicamente hizo una excepción con la Compañía Neerlandesa de Indias Orientales, quienes tuvieron el privilegio de ser los únicos europeos con acceso al archipiélago japonés. Gracias a esta prerrogativa, entre 1690 y 1692, el médico alemán Engelbert Kaempfer pudo visitar el País del Sol Naciente, viajando en hasta dos ocasiones a la corte del sogún en Edo (Tokio). Fruto de estas experiencias, el germano pudo tomar una serie de notas y dibujos retratando diversos aspectos de las inaccesibles islas. Muchos de estos materiales se publicaron posteriormente en su obra The History of Japan (Londres, 1727), sin embargo una gran cantidad de sus diseños, de un valor histórico incalculable, quedaron sin editar en las sombras de sus archivos. A continuación trataremos de arrojar luz sobre estos insólitos bocetos e ilustraciones.